ChemInform Abstract: Unprecedented Electron‐Poor Octahedral Ta6 Clusters in a Solid‐State Compound: Synthesis, Characterizations and Theoretical Investigations of Cs2BaTa6Br15O3. Issue 51 (17th December 2013) - Demont, Antoine; Prestipino, Carmelo; Hernandez, Olivier; Elkaim, Erik; Paofai, Serge; Naumov, Nikolai; Fontaine, Bruno; Gautier, Regis; Cordier, Stephane
Abstract Cs2BaTa6Br15O3 and Cs2LaTa6Br15O3 are obtained from stoichiometric mixtures of Ta, Ta2O5, TaBr5, CsCl, and BaBr2 or La2O3 (sealed silica container, 650—690 °C, 3 d).